2018
DOI: 10.1177/1526602818819501
|View full text |Cite
|
Sign up to set email alerts
|

Air Embolism During TEVAR: Liquid Perfluorocarbon Absorbs Carbon Dioxide in a Combined Flushing Technique and Decreases the Amount of Gas Released From Thoracic Stent-Grafts During Deployment in an Experimental Setting

Abstract: To investigate the influence of flushing thoracic stent-grafts with carbon dioxide and perfluorocarbon on the amount of gas released during stent-graft deployment in thoracic endovascular aortic repair (TEVAR). Materials and Methods: Ten TX2 ProForm thoracic stent-grafts were deployed into a water-filled container with a curved plastic pipe and flushed sequentially with carbon dioxide, 20 mL of liquid perfluorocarbon (PFC), and 60 mL of saline. Released gas was measured using a calibrated setup. The volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
2
32
0
2
Order By: Relevance
“…A dynamic bubble trap designed to reduce gaseous emboli has been shown to reduce TCD HITS, and cognitive function 3 months after surgery was significantly better compared with that in control patients undergoing coronary artery bypass grafting 40 . It has also been demonstrated that thoracic endografts release significant amounts of air during deployment if flushed according to the instructions for use, and carbon dioxide flushing before standard saline flushing significantly reduces the amount of gas released 41 . This may have a potential role in reducing air embolism during TEVAR, particularly in more proximal landing zones 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A dynamic bubble trap designed to reduce gaseous emboli has been shown to reduce TCD HITS, and cognitive function 3 months after surgery was significantly better compared with that in control patients undergoing coronary artery bypass grafting 40 . It has also been demonstrated that thoracic endografts release significant amounts of air during deployment if flushed according to the instructions for use, and carbon dioxide flushing before standard saline flushing significantly reduces the amount of gas released 41 . This may have a potential role in reducing air embolism during TEVAR, particularly in more proximal landing zones 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Released air from the stent-graft was collected in the supra-aortic branches separately with 1-mL syringes and measured in 0.01-mL increments, as previously reported. 9 The air from the ascending and descending aorta was collected separately with a catheter and measured with a 1-mL syringe ( Figure 2).…”
Section: Aortic Flow Model and Stent-graftsmentioning
confidence: 99%
“…6 Recent in vitro studies demonstrated air release from angiographic catheters and during deployment of different TEVAR devices, with a potential risk for air embolization in the supra-aortic arteries. [7][8][9] Grover et al 10 showed in vivo that 90% of MES in MCA during TEVAR are caused by air emboli, and the highest number was measured during stentgraft deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Eine wesentliche Rolle kommt aber auch der Freisetzung der Stentgrafts zu: durch die aufwändige Verpackung der Stentgrafts in den Schleusenhülsen kann auch eine sorgfältige Spülung der Prothese keine vollständige Entlüftung erreichen. Aus diesem Grund wurde eine Technik der zusätzlichen CO2-Spülung entwickelt, mit der die Rate an Luftembolien deutlich reduziert werden konnte (Kölbel et al 2016;Rohlffs et al 2018Rohlffs et al , 2019.…”
Section: Luftembolieunclassified